Makna Tari Sada-Sabai Dalam Upacara Pernikahan Masyarakat Komering Martapura, OKU Timur - Indah Pebriyanti (Tanjak: Sejarah dan Peradaban Islam, 2022)
Indonesia is a country with many different cultures and customs in it. One of them, the Sada Sabay Dance, which is one of the typical dances of the Komering Tribe in Ogan Komering Ulu Timur Regency, South Sumatra. This dance is performed when the wedding ceremony takes place, this dance is not only performed when fellow Komering tribes are married. The Sada Sabay dance is still carried out under three conditions of marriage, namely Komering tribal women with Komering tribal men, Komering tribal women with non-Komering tribal men, and non-Komering tribal women with Komering tribal men. The Sada Sabay dance is performed during the main event of the wedding ceremony, this dance is performed by the parents of the bride and groom and the bride and groom position behind their in-laws with a fan position towards their in-laws. The Sada Sabay dance is interpreted as a family dance, a dance of happiness, and a form of gratitude for having a new family from their children's marriage. It is known that this dance has been carried out since the days of the ancestors of the previous Komering tribe, it's just that there has been a change in the accompanying music. In the past, the accompaniment of this dance was still in the form of a traditional musical instrument called the Kulintang, along with the development of the times, the Sada Sabay dance was performed to the accompaniment of single organ music, but there are still places where the Sada Sabay dance is performed with the accompaniment of traditional Kulintang music.